Exploring the Impact of Emotional Intelligence on Collaboration Styles in Interpersonal Conflict Management among Adolescents - Christa , Marielle (Educational Studies and Research Journal, 2024)
The primary objective of this research is to investigate the correlation between emotional intelligence and collaboration styles in the resolution of interpersonal conflicts among adolescents. A direct association is observed, wherein heightened emotional intelligence corresponds to a more positive collaboration style in handling interpersonal conflicts, while diminished emotional intelligence aligns with a more negative collaboration approach. The study involved adolescents aged 16 to 18 years, employing the Try-out technique for subject retrieval. The researcher developed a collaboration style scale for managing interpersonal conflicts among adolescents, referencing Thomas Kilmann Inventory. Additionally, an emotional intelligence scale, inspired by Goleman's theory (2001), was created by the researcher. Data analysis was conducted using the SPSS for Windows Version 15.00 program, confirming a statistically significant relationship between emotional intelligence and collaboration style in managing interpersonal conflicts among adolescents. The Pearson product-moment correlation revealed a coefficient of r = 0.808 with p = 0.000 (p < 0.01), indicating a highly significant association. Consequently, the research hypothesis is accepted.